Analysis of spirometry results in hospitalized patients aged over 65 years - Wróblewska I (Dove Medical Press, 2015)
Izabela Wróblewska,1 Piotr Oleśniewicz,2 Donata Kurpas,3 Mariusz Sołtysik,2 Jerzy Błaszczuk41Faculty of Health Science, Wroclaw Medical University, 2Institute of Tourism and Recreation, University School of Physical Education in Wroclaw, 3Department of Family Medicine, 4Faculty of Postgraduate Medical Training, Wroclaw Medical University, Wroclaw, Lower Silesia, PolandIntroduction and objective: The growing population of the elderly, as well as the occurrence of coexisting diseases and polypharmacy, is the reason why diseases of patients aged ≥65 years belong to the major issues of the contemporary medicine. Among the most frequent diseases of the elderly, there are respiratory system diseases. They are difficult to diagnose because of the patient group specificity, which is the reason for increased mortality among seniors, caused by underdiagnosis. The study objective was to assess the factors influencing spirometry results in hospitalized patients aged ≥65 years with respiratory system disorders.Material and methods: In the research, 217 (100%) patients aged ≥65 years who underwent spirometry at the Regional Medical Center of the Jelenia Góra Valley Hospital in Poland were analyzed. In the statistical analysis, the STATISTICA 9.1 program, the t-test, the Shapiro–Wilk test, the ANOVA test, and the Scheffé’s test were applied.Results: The majority of the patients (59.4%) were treated in the hospital. The most frequent diagnosis was malignant neoplasm (18%). The study showed a statistically significant dependence between the forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and FEV1/FVC parameters and the time of hospitalization, as well as between the FVC and FEV1 parameters and the age of patients. The FVC parameter values turned out to be dependent on the main diagnosis. Highest results were noted in patients with the diagnosis of sleep apnea or benign neoplasm. A low FVC index can reflect restrictive ventilation defects, which was supported by the performed analyses. Highest FEV1/FVC values were observed in nonsmokers, which confirms the influence of nicotine addiction on the incidence of respiratory system diseases.Conclusion: The respondents’ sex and the established diagnosis statistically significantly influenced the FVC index result, and the diet influenced the FEV1/FVC parameter result.Keywords: the elderly, spirometry, respiratory system diseases